The effect of voluntary disclosure, foreign ownership and institutional ownership on long term debt in coal mining sub-sector companies listed on the Indonesia stock exchange - Al Hatul Julianti; Rizky Yudaruddin (Faculty of Economics and Business Mulawarman University, 2023)
This study aims to analyze the effect of voluntary disclosure, foreign ownership, and institutional ownership on long derm debt in coal mining sub-sector companies listed on the Indonesia Stock Exchange. Using the purposive sampling method, 18 companies were obtained as research samples with 2016 to 2018 used as the research period. The analysis method used is to use panel data regression analysis assisted by using statistical analysis tools, namely Eviews. The results showed that: (1) voluntary disclosure has a negative and significant effect on long derm debt in coal mining companies listed on the Indonesia Stock Exchange. (2) foreign ownership has a negative and significant effect on long derm debt in coal mining companies listed on the Indonesia Stock Exchange. (3) institutional ownership has a positive and insignificant effect on long derm debt in coal mining companies listed on the Indonesia Stock Exchange.